Role of the internet as an information resource before anaesthesia consultation: A French prospective multicentre survey. Issue 12 (December 2017) - Nucci, Bastian; Claret, Pierre-Geraud; Leclerc, Gilles; Chaumeron, Arnaud; Grillo, Philippe; Buleon, Clément; Leprince, Vincent; Raux, Mathieu; Minville, Vincent; Futier, Emmanuel; Lefrant, Jean-Yves; Cuvillon, Philippe
Abstract : BACKGROUND: Use of the internet as an information search tool has increased dramatically. Our study assessed preoperative use of the internet by patients to search for information regarding anaesthesia, surgery, pain or outcomes. OBJECTIVE(S): The aim of this study was to test whether patients used the internet prior to surgery and what kinds of information they looked for (anaesthetic technique, pain, adverse events, outcomes and surgery). Correlation between patient age and information sought about surgery from the internet was also explored. DESIGN: A prospective multicentre observational study. SETTING: In total, 14 French private and public institutions from May 2015 to January 2016. PATIENTS: In total, 3161 adult patients scheduled for elective surgery under regional or general anaesthesia. INTERVENTION(S): An anonymous questionnaire was presented to adult patients scheduled for elective surgery under regional or general anaesthesia for completion before the first meeting with the anaesthesiologist. The investigator at each centre completed specific items that the patient could not complete. MAIN OUTCOME MEASURES: We defined the primary endpoint as the number of patients who searched for information about their anaesthesia or surgery on the internet by the time of the their preanaesthetic consultation. RESULTS: Of the 3234 questionnaires distributed, responses were received from 3161 patients. Within this respondent sample, 1304 (45%) were professionally active and 1664 (59%) used the internet at least once per day. Among 3098 (98%) patients who answered the question concerning the primary endpoint, 1506 (48%) had searched the internet for information about their health. In total, 784 (25%) used the internet to find information about their surgery and 113 (3.5%) looked for specific information about anaesthesia. Of the 3161, 52% reported difficulty searching for appropriate information about anaesthesia on the internet. 'Daily use of the web' [odds ratio (OR) 2.0; (95% CI: 1.65 to 2.55) P  < 0.001], 'use of the web on mobile devices' [OR 1.24; (95% CI: 1.02 to 1.50) P  = 0.02] and 'asking general practitioner or surgeon about information' [OR 1.35; (95% CI: 1.11 to 1.64) P  = 0.002] were significantly associated with the primary endpoint. CONCLUSION: The internet was not widely used by patients scheduled for elective surgery to search for information about anaesthesia and surgery in our French multicentre study. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT02442609. Abstract : Supplemental Digital Content is available in the text